The effect of the contrast between the digital textual and digital sound descriptors of virtual museum pieces in developing the cognitive and academic achievement of intermediate students of the components of the computer - Al-Harbi, Abdul Hakim Saleh; Al Manakhrah, Hassan Yahya Saadi (Journal of Educational and Psychological Sciences, 2019)
This research aimed to identify the contrast between the digital textual and digital sound descriptors of virtual museum pieces in developing the cognitive and academic achievement of intermediate students of the components of the computer. The researcher used the descriptive and the semi-experimental method which relies on experiment on two groups. The first group is subjected to study in Virtual Museum with script digital description for the museums pieces, and the second is subjected to study in Virtual Museum with visual description for the museums pieces. The achievement test was the tool of the study, the sample of the study consisted of (50) student from the first grade in Al-Jazeera intermediate school in Buraydah, and the students were distributed into two groups each group consisted of (25) students. The results of the study showed that there was statistically significant difference between (0.01) between the average scores of the two experimental groups in the educational achievement test due to the main effect of the difference between the audio descriptions and textual descriptions of the virtual museums for the experimental group (1) which uses a default digital textual description of the museum. The researcher recommends the need to utilize from the results in: Improve education for intermediate students of computer components, by using virtual museums. And provide a teaching guide to the teachers helps to employ virtual museums to improve teaching performance.